Nowoczesne formy doskonalenia kadry zarządzającej - Zawora, Paweł (Innovate Forms of Management Skills Improvement, 2008)
Analyzing and directing emotions, observational skills and prediction skills, responsibility and consequence are helpful in building authority based on trust. The necessity for possession of such skills for leading team is obvious. If leaders will find in themselves enough humility and will power to make decision to stand next to a horse and lead it, they will find out that the possessed skills should be strengthened, sharpened, some will require correction or total elimination. Besides humility one has to be enthusiastic in undertaking new and unfamiliar tasks. Openness, kindness and creative attitude are also fundamental features of a good leader. It is possible to train, educate or to manage and not possess those features-proceeding like poor craftsmen or choose another road of constant improvement, becoming virtuoso in the specific area of expertise. Horses could be a great help in achieving this goal.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 192-201